Caracterização geoquímica e geocronológica do complexo Jequitinhonha na área tipo, Orógeno Araçuaí - Tatiana Gonçalves Dias (2012)
The Jequitinhonha Complex is one of the most extensive metasedimentary units of the Araçuaí Orogen internal domain, in southeastern Brazil. In its type-area, between Jequitinhonha and Almenara (MG), it is composed of migmatized peraluminous (kinzigitic) paragneiss with intercalations of quartzite, graphite gneiss, calcsilicate and metabasics rocks. The kinzigitic gneisses are typically rich in Al2O3 (11.49%19.80%), with SiO2=57.82%75.93%, K2O=0.24%4.93%, Na2O=0.873.24% e CaO=0.33-6.85%, reflecting predominance of pelitic contribution. The major element attributes suggest graywacky pelite and graywacke to most paragneiss protoliths. Chondrite-normalized rare earth elements patterns (REE) shows moderated enrichment in light rareearth elements (LaN/YbN = 6.67-14.38) and a prominent negative Eu anomaly (Eu/Eu* = 0.52-0.81), which are similar to NASC and comparable to passive margin turbidite patterns. Th/Sc ratios in between 0.58 and 1.08 also suggest the reworking of evolved continental crust as the main source for the protoliths. The analysis of the detrital zircon U-Pb age spectra (LA-ICP-MS) from two quartzite samples allows to identify six main age peaks in the source areas of the Jequitinhonha Complex, at around 950, 1200, 1500, 1800, 2000 and 2500 Ma. The youngest detrital zircon found and the age of granulite-facies regional metamorphism in the area brackets the deposition of the protoliths in between 898 and 575 Ma. The Nd isotopic signatures of the kinzigitic gneisses are very homogeneous, with Tdm in between 1.6 - 1.8 Ga and Nd(575 Ma) from -7.0 to -7.9. The isotopic data suggest the predominance of Paleoproterozoic crust, mixed with smaller amounts of Meso to Neoproterozoic crust, in the Jequitinhonha Complex source areas, which involve the São Francisco Craton basement, the Juiz de Fora and Mantiqueira complexes (~2.0 Ga), and the tonian rift-related magmatic rocks, especially the thick volcanic sequence of the West Congo Fold Belt (~1.0-0.9 Ga). The Jequitinhonha Complex can be correlated to the upper Macaúbas Group, which show similar detrital zircon age spectra and Nd isotopic signatures. Therefore, as suggested by the lithochemical and isotopic data, the Jequitinhonha Complex protoliths are probably deposited in the distal passive margin of the precursor basin to the Araçuaí Orogen.